Experimental investigation on shear strengthening of RC beams using advanced fibre-reinforced cementitious composites - Xiangsheng Liu; Osamah Karaghool; Georgia E. Thermou; Jing Yu (Case Studies in Construction Materials, 2025)
The increasing demand for durable marine and coastal structures has motivated research into advanced shear strengthening methods that offer both mechanical efficiency and optimized material usage. This research presents an experimental evaluation of three shear retrofitting strategies for reinforced concrete beams: High-Tensile-Strength Strain-Hardening Cementitious Composites (HTS-SHCC), Ultra-High-Performance Concrete (UHPC), and a hybrid UHPC system reinforced with Ultra-High-Tensile-Strength Steel (UHTSS) textiles. Seven reinforced concrete (RC) beams, including one control specimen, were subjected to three-point bending tests to examine the effects of key strengthening variables, including UHTSS textile density (1.57 and 3.14 cords/cm), cementitious composites (HTS-SHCC and UHPC), and jacketing thickness (10 mm and 20 mm). Results demonstrate that all strengthening systems significantly improved shear capacity by 53.2 %-83.2 %, with the hybrid system combining high-density UHTSS achieving the highest increase. While HTS-SHCC specimens exhibited greater shear strength than their UHPC counterparts, the latter demonstrated superior pseudo-ductile behaviour through progressive crack dispersion. All strengthened beams failed in shear detachment, though the hybrid system experienced larger-scale concrete cover peeling due to stress redistribution induced by UHTSS textiles. The findings underscore the potential of advanced cementitious composites and hybrid solutions to balance strength, ductility, and retrofit practicality in shear-critical RC structures.